Neuropeptide Receptors in Intestinal Disease: Physiology and Therapeutic Potential - Snoek, Susanne A.; Borensztajn, Keren S.; van den Wijngaard, Rene M.; de Jonge, Wouter J. (Current Pharmaceutical Design, 2010)
The autonomous nervous system of the gut is increasingly recognized as an important regulatory factor in intestinal permeability and immune cell activation. Neuropeptides released by neurons -or inflammatory cells- have emerged as neuro-immune modulators that can relay, for instance, stress-induced neuronal activity to immune processes. Such peptides can participate in processes reducing inflammatory responses, or augment resolution of inflammation. Neuropeptides and hormones such as vasoactive intestinal peptide, urocortin, ghrelin, and cortistatin have been shown to modulate the disease activity in a variety of experimental models of inflammatory and autoimmune disease via modulation of immune or neuronal cell activity. We review here the potential of neuropeptide receptor activation to modulate inflammatory diseases. We will highlight the role of neuropeptides in gastrointestinal (GI) physiology and immune regulation, and we will speculate on the therapeutic potential of peptides that bind G protein coupled receptors (GPCRs) in the management of inflammation in the GI tract.
Keywords: intestine